2009
DOI: 10.20965/jaciii.2009.p0283
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Scissors in a Thin Haptic and Force Feedback Environment

Abstract: The virtual scissors using virtual hands we propose enable users can cut virtual paper with their own hands. One purpose of our proposal is to facilitate implementing different tools simply by changing software parameters. Another is to make a general-purpose system with small-scale input and output devices for general applications, e.g., only using thin haptic information and force feedback. With such virtual reality (VR) scissors, we introduced feedback to cover any impressions such as interface interfere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Funahashi et al reported that vibration and sound feedback in scissors used in VR environments are effective in providing a sense of reality [ 5 ]. Okamura et al, in a study that modeled VR scissors with tactile feedback in terms of friction, motion, and physical properties, showed that users could feel the cutting force as if the model were actual scissors, even if the cutting force was not very precise [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Funahashi et al reported that vibration and sound feedback in scissors used in VR environments are effective in providing a sense of reality [ 5 ]. Okamura et al, in a study that modeled VR scissors with tactile feedback in terms of friction, motion, and physical properties, showed that users could feel the cutting force as if the model were actual scissors, even if the cutting force was not very precise [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research on scissors used in surgery has undergone a resurgence due to the need for virtual reality (VR) systems and surgical robot development [3][4][5][6][7]. Ergonomics has also been considered for scissors in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported that fluctuations in frictional resistance occur on the finger surface of humans and cause a stick-slip feeling [15,[18][19][20]. Funahashi et al reported that vibration feedback heightened the reality of virtual cutting [14]. It was suggested that dry, creaking, and hard feels were derived from fine fluctuations of F xy .…”
Section: Discussionmentioning
confidence: 99%
“…The calculated forces were displayed by a 2 degree-of-freedom haptic scissors system [13]. Funahashi et al displayed cutting sensation by combining vibrations and cutting sound [14].Scissors and forceps are used not only for cutting, but also for grasping objects. In this study, the mechanical stimuli were measured when a test subject grasped or cut an object with scissors.…”
mentioning
confidence: 99%
See 1 more Smart Citation